2013
DOI: 10.1016/j.envpol.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations and potential sources of PCBs, PBDEs, and pesticides to Acadia National Park

Abstract: a b s t r a c tThis study assessed concentrations and investigated potential source regions for PCBs, PBDEs, and organochlorine pesticides in Acadia National Park, Maine, USA. Back-trajectories and potential source contribution function (PSCF) values were used to map potential source areas for total-PCBs, BDE-47, and 10 organochlorine pesticides. The constructed PSCF maps showed that ANP receives high pollutant concentrations in air masses that travel along four main pathways: (1) from the SW along the eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…13 C 12 -PBDEs, 13 C 6 -HBBz, 13 C 12 -TBBPA, 13 C 12 -γ-HBCD, 13 C 12 -Triclsoan and 13 C 12 -MTCS were purchased from Wellington Laboratories (Ontario, Canada). 4-n-Nonylphenol-2, 3, 5, 6-d 4 …”
Section: Chemicals and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C 12 -PBDEs, 13 C 6 -HBBz, 13 C 12 -TBBPA, 13 C 12 -γ-HBCD, 13 C 12 -Triclsoan and 13 C 12 -MTCS were purchased from Wellington Laboratories (Ontario, Canada). 4-n-Nonylphenol-2, 3, 5, 6-d 4 …”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Despite strong regulatory action to eliminate or control emissions of persistent organic pollutants (POPs), polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) remain ubiquitous environmental contaminants, worldwide [1][2][3][4] . In recent years, other emerging organic contaminants (EOCs) have received increasing attention, including halogenated flame retardants (HFRs) such as polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCD), and dechlorane plus (DP), as well as synthetic musks (galaxolide, tonalide, musk ketone, musk xylene) and the antibacterial agent, triclosan [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PBDEs in the atmosphere can enter the human body through the respiratory tract (inhalation and dust ingestion), and become concentrated in the human body (Fitzgerald et al, 2012;Yu et al, 2012;Arellano et al, 2013;Krol et al, 2014). Previous studies have shown that high concentrations of PBDEs may be associated with their transport patterns (Sofuoglu et al, 2013), or may originate from emissions from products, especially electrical equipment (Zhang et al, 2011;Birgul et al, 2012). Moreover, many studies have demonstrated that PBDE pollution in industrial or urban areas is much higher than in rural areas (Zhang et al, 2008;Syed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Different trajectory statistics methods have been used to reveal the region sources of sulphur oxides and sulphates (Ashbaugh, Malm, and Sadeh 1985;Rúa et al 1998;Zhao, Hopke, and Zhou 2007;Stohl 1996;Poirot and Wishinski 1986), nitrogen oxides and nitrates (Rúa et al 1998;Zhao, Hopke, and Zhou 2007), ozone (Wotawa, Kröger, and Stohl 2000), acid precipitations (Charron et al 2000), aerosol (Seibert et al 1994;Wang, Zhang, and Arimoto 2006;Chen et al 2011;Zhou, Hopke, and Liu 2004;Zhao and Hopke 2006;Tositti et al 2013;Xu et al 2013;Aher et al 2014), sources and sinks of CO 2 (Apadula et al 2003), radioactive Ве 7 (Lee et al 2004), soot particles (Sharma et al 2006), and persistent organic pollutants (Du and Rodenburg 2007;Hsu, Holsena, and Hopke 2003;Sofuoglu et al 2013) in different areas of the planet.…”
Section: Introductionmentioning
confidence: 99%